Analysis of the Role of Quality of Work Life on the Performance of Village Officials Based on Leadership and Motivation (International Journal of Economics and Management Research, 2025)
This study aims to determine the effect of Leadership and Motivation Analysis on the Performance of Village Officials Mediated by Quality of Work Life. The population in this study were village officials in Lawang Subdistrict, Malang Regency. The sampling technique used in this study was total sampling with a total of 105 respondents. The data was processed using Smart Partial Least Square 4 (PLS) software. Based on the results of the data analysis, the following conclusions can be drawn: Low leadership and motivation have not been able to contribute to improving the performance of village officials. Likewise, better leadership and motivation can contribute to the quality of work life. This study also found that a better quality of work life will contribute to the performance of village officials. Furthermore, high or improved leadership and motivation, accompanied by a good quality of work life, will improve the performance of village officials.